Performance Of Retirement Submission Services At The Civil Service And Human Resources Development Agency (BKPSDM) Of Aceh Tengah Regency, Aceh Province - Rosida Takechin Br Sianturi; Wirman Syafri; Rizki Amalia (Jurnal Scientia, 2024)
The purpose of this study was to analyse the Performance of Pension Submission Services at the Central Aceh Regency Personnel and Human Resources Development Agency, analyse the inhibiting and supporting factors for the Performance of Pension Submission Services at the Central Aceh Regency Personnel and Human Resources Development Agency and analyse efforts in overcoming inhibiting factors in the Performance of Pension Submission Services at the Central Aceh Regency Personnel and Human Resources Development Agency. This research method uses a qualitative research method descriptive approach. The data collection techniques used are interviews, observation, and documentation. The informants in this study were 17 (seventeen) people who were determined by purposive sampling and snowball techniques. The data analysis techniques used are data reduction, data presentation and conclusion drawing which ends with data validation using source triangulation. Based on the results of research and discussion, it can be concluded that the performance of the Central Aceh Regency Personnel and Human Resources Development Agency in pension application services has been running quite well, this can be seen from the aspects of service quality, responsiveness and accountability although there are still shortcomings in the aspects of productivity and responsibility that have not gone well. The supporting factors in the retirement application service are the ability of officers to provide services, comfort in the service environment, the availability of guidebooks and the existence of application-based digital platforms with inhibiting factors, namely the lack of human resources, lack of mastery of digital technology, inadequate facilities and infrastructure, limited budget and lack of discipline and work motivation. The efforts made by BKPSDM Aceh Tengah Regency are proposing additional human resources, attending digital skills training, using personal laptops, increasing the budget and implementing a system of rewards and consequences.